2004
DOI: 10.1002/jcp.10476
|View full text |Cite
|
Sign up to set email alerts
|

A role for lysyl oxidase regulation in the control of normal collagen deposition in differentiating osteoblast cultures

Abstract: Differentiation of phenotypically normal osteoblast cultures leads to formation of a bone-like extracellular matrix in vitro. Maximum collagen synthesis occurs early in the life of these cultures, whereas insoluble collagen deposition occurs later and is accompanied by a diminished rate of collagen synthesis. The mechanisms that control collagen deposition seem likely to include regulation of extracellular collagen biosynthetic enzymes, but expression patterns of these enzymes in differentiating osteoblasts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 53 publications
11
84
2
Order By: Relevance
“…[30][31][32] However, it remains unclear if dexamethasone can selectively induce apoptosis of some populations of bone marrow cells which were thought to have poor differentiation capability as suggested by Oshina et al 33 or if glucocorticoids fail to induce terminal osteoblast differentitation. 34 Our results also corresponded to Hong et al 35 who reported an early expression but a late secretion and deposition of collagen I in osteoblast cultures. We found significant peaks of collagen I in DAG and DAG þ BMP-2-stimulated cultures but not in controls at day 28, whereas the collagen I levels in culture media showed no significant differences at days 4 and 14.…”
Section: Discussionsupporting
confidence: 91%
“…[30][31][32] However, it remains unclear if dexamethasone can selectively induce apoptosis of some populations of bone marrow cells which were thought to have poor differentiation capability as suggested by Oshina et al 33 or if glucocorticoids fail to induce terminal osteoblast differentitation. 34 Our results also corresponded to Hong et al 35 who reported an early expression but a late secretion and deposition of collagen I in osteoblast cultures. We found significant peaks of collagen I in DAG and DAG þ BMP-2-stimulated cultures but not in controls at day 28, whereas the collagen I levels in culture media showed no significant differences at days 4 and 14.…”
Section: Discussionsupporting
confidence: 91%
“…SDS PAGE stained with Coomassie Blue R250 revealed a single band with an apparent molecular size of 35 kDa that is fully consistent with our published studies [7]. In selected experiments LOX-PP expressed in bacteria was utilized [9].…”
Section: Recombinant Lysyl Oxidase Propeptidesupporting
confidence: 87%
“…The tumor suppressor activity of LOX has been mapped to the pro-peptide region [24] and LOX-PP inhibits tumor formation by breast cancer cells in mice [19]. In normal osteoblasts, LOX-PP accumulates in cultures [9] and recombinant LOX-PP is taken up by cells and accumulates over time associated with microtubules [7]. LOX is critically important for development of a normal cardiovascular system [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations